Mussel-inspired injectable hydrogel and its counterpart for actuating proliferation and neuronal differentiation of retinal progenitor cells. (February 2019) - Tang, Zhimin; Jiang, Fang; Zhang, Yuanhao; Zhang, Yi; YuanYang,; Huang, Xiaolin; Wang, Yuyao; Zhang, Dandan; Ni, Ni; Liu, Feng; Luo, Min; Fan, Xianqun; et al.
Abstract: Biomaterials-mediated retinal progenitor cell (RPC)-based transplantation therapy has shown substantial potential for retinal degeneration (RD), but it is limited by the poor RPC survival, proliferation and differentiation. Herein, the gelatin-hyaluronic acid (Gel-HA)-based hydrogels formed via moderate Michael-type addition reaction with or without the introduction of mussel-inspired polydopamine (PDA), i.e. Gel-HA-PDA and its counterpart Gel-HA hydrogels are developed, and their effects on the biological behaviour of RPCs, including adhesion, survival, proliferation, differentiation, delivery and migration are investigated. The hybrid hydrogels can adopt the intricate structure of the retina with suitable mechanical strength, degradation rate and biological activity to support cellular adhesion, survival and delivery. Meanwhile, Gel-HA hydrogel can remarkably promote RPC proliferation with much larger cell clusters, while Gel-HA-PDA hydrogel significantly enhances RPC adhesion and migration, and directs RPCs to preferentially differentiate toward retinal neurons such as photoreceptors (the most crucial cell-type for RD treatment), which is mainly induced by the activation of integrin α5β1-phosphatidylinositol-3-kinase (PI3K) pathway. This study demonstrates that Gel-HA hydrogel possesses great potential for RPC proliferation, while mussel-inspired PDA-modified Gel-HA hydrogel with superior biocompatibility can significantly promote RPC neuronal differentiation, providing new insights for developing biomedical materials applied for RPC-based transplantation therapy.